Zika, chikungunya, and dengue viral infections in human peripheral blood mononuclear cells: cell susceptibility and gene expression (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Infections of Zika (ZIKV), dengue (DENV), and chikungunya viruses (CHIKV) are presented with similar clinical symptoms; these often lead to misdiagnosis. Viremia levels and host immune responses may contribute to disease severity. This study was aimed to characterize the ability of ZIKV, CHIKV, and DENV to infect human peripheral blood mononuclear cells (PBMCs) and assess the expression of tumor necrosis factor (TNF)-α, interleukin (IL)-10, and interferon gamma-induced protein (IP)-10 genes in response to the viral infections. METHODS PBMCs were isolated from healthy donors using gradient centrifugation. Cells were infected with Indonesian isolates of ZIKV, CHIKV, and DENV for 48 hours. Plaque assays were performed to measure viable virus titers, while viral genomic RNA and the gene expression of TNF-α, IL-10, and IP-10 were determined using real-time quantitative reverse transcription-polymerase chain reaction. RESULTS The susceptibility of PBMCs to ZIKV, CHIKV, and DENV infection was observed, and the viable virus titer and viral genome quantity were found to be significantly higher in ZIKV and CHIKV. All viruses induced the expression of immune-related proteins. The TNF-α gene was upregulated by all viruses to relatively similar levels. IL-10 expression was highest in response to ZIKV, followed by CHIKV. In contrast, IP-10 expression was highly upregulated in DENV-infected cells and only moderately expressed in ZIKV- and CHIKV-infected cells. CONCLUSIONS ZIKV, CHIKV, and DENV clinical isolates infected PBMCs with different levels of virus infectivity. The gene expression of IL-10 was highly upregulated in ZIKV infection and IP-10 in DENV infection.